The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5424/sjar/2016142-7562
|View full text |Cite
|
Sign up to set email alerts
|

Application of electrical capacitance measurement for in situ monitoring of competitive interactions between maize and weed plants

Abstract: Applicability of root electrical capacitance (EC) measurement for monitoring of crop–weed competition was studied in a pot experiment. Maize (Zea mays L.) was grown both alone and with Echinochloa crus-galli or Abutilon theophrasti in different densities with regular measurement of root EC. Plants were harvested 42 days after planting to determine above- and belowground biomass. Depending on weed density, E. crus-galli-A. theophrasti interaction reduced the root EC of maize by 22–66% and 3–57%, respectively. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The strong species dependence of the relationship between C rel and θ rel is in accordance with the species- and substrate-specific nature of the C R –RSS relationships reported in previous papers (Chloupek et al, 2010 ) and also found in the present study (Figure 1 ). The positive intercept derives from electrode polarization and the capacitance of the plant stem base (Cseresnyés et al, 2016b ), and it is thought to be a function of SWC (Ozier-Lafontaine and Bajazet, 2005 ; McBride et al, 2008 ). The changes in C rel in relation to θ rel for a given species are also likely to be influenced by the soil type, but further investigations are required to assess this effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong species dependence of the relationship between C rel and θ rel is in accordance with the species- and substrate-specific nature of the C R –RSS relationships reported in previous papers (Chloupek et al, 2010 ) and also found in the present study (Figure 1 ). The positive intercept derives from electrode polarization and the capacitance of the plant stem base (Cseresnyés et al, 2016b ), and it is thought to be a function of SWC (Ozier-Lafontaine and Bajazet, 2005 ; McBride et al, 2008 ). The changes in C rel in relation to θ rel for a given species are also likely to be influenced by the soil type, but further investigations are required to assess this effect.…”
Section: Discussionmentioning
confidence: 99%
“…The C R method was used to develop specific calibration relationships with reasonable predictive ability to obtain an absolute measurement of root traits for a given plant grown in a given soil (Preston et al, 2004 ; McBride et al, 2008 ; Tsukahara et al, 2009 ; Pitre et al, 2010 ). The technique was also applied without specific calibration for the comparison of RSS when studying plant responses to environmental stresses (e.g., herbicide treatment, heavy metal contamination, weed competition) and arbuscular mycorrhizal fungi (AMF) colonization, and to monitor cultivar-specific differences in root growth dynamics (Vamerali et al, 2009 ; Cseresnyés et al, 2012 , 2013 , 2016a , b ). Chloupek et al ( 2010 ) emphasized that “C R data are only comparable for plants of the same species, grown in the same substrate at the same moisture level.” The non-intrusive capacitance method is appropriate for repeated evaluation of the same plant population at different ontogenetic phases, provided that SWC in the pots is identical at each measurement time.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of root development with time using ECM showed that there are important temporal variations in the measured capacitance (Cseresnyés et al., 2018; Cseresnyés, Rajkai, & Takács, 2016; Cseresnyés, Takács, Füzy, & Rajkai, 2014; Cseresnyés, Takács, Füzy, Végh, & Lehoczky, 2016; Dalton, 1995). Cseresnyés et al.…”
Section: Methods Targeting Electrical Resistivitymentioning
confidence: 99%
“…Investigations of root development with time using ECM showed that there are important temporal variations in the measured capacitance (Cseresnyés et al, 2018;Cseresnyés, Rajkai, & Takács, 2016;Cseresnyés, Takács, Füzy, & Rajkai, 2014;Cseresnyés, Takács, Füzy, Végh, & Lehoczky, 2016;Dalton, 1995). Cseresnyés et al (2014) found that root water uptake and C root increased from the emergence of a seedling to the beginning of flowering and then decreased continuously during the fruit setting for cucumber (Cucumis sativus L.) and bean (Phaseolus vulgaris L.).…”
Section: Ecm On Single Plants In Soilmentioning
confidence: 99%